Prevalence of the NTEKPC-I on IncF Plasmids Among Hypervirulent Klebsiella pneumoniae Isolates in Jiangxi Province, South China - Huang, Qi-Sen; Liao, Wenjian; Xiong, Zhijuan; Li, Dan; Du, Fang-Ling; Xiang, Tian-xin; Wei, DanDan; Wan, La-Gen; Liu, Yang; Zhang, Wei (Frontiers in Microbiology, 2021)
Infection caused by carbapenem-resistant hypervirulent Klebsiella pneumoniae(CR-hvKP) has become a tricky healthcare threat in China and KPC-2 enzyme is a main factor mediating resistance to carbapenems of K. pneumoniae. Here, we report the characterization of the genetic environment of blaKPC-2 gene in CR-hvKP clinical isolates from South China. Forty-five nonduplicated CR-hvKP isolates collected in Jiangxi Province from 2018 to 2019 were analyzed. Each of them were multidrug-resistant due to the presence of not only blaKPC-2 gene but also other resistance determinants, including Metallo-β-lactamases(NDM-1), extended-spectrum β-lactamases(TEM-1, CTX-M-14, SHV-1), and plasmid-mediated quinolone resistance determinants(qnrS, aac(6’)-Ib-cr). After plasmid analyses of PCR-based replicon typing (PBRT), mapping PCR, amplicon sequencing, and whole-genome sequencing(WGS) were used to analyze the genetic environment of the blaKPC-2 gene. PCR analysis of pLVPK-like plasmids, Southern Blot, and mouse lethality assay were used to assess the virulence phenotype of K. pneumoniae. Multilocus sequence typing (MLST) analysis showed ST11 CR-hvKP was the predominant clone. In conclusion, This is the first analysis of diverse genetic structures blaKPC-2 gene in CR-hvKP isolates from south China. Both the NTEKPC-I on the IncF plasmids and pLVPK-like virulence plasmids make contributions to the formation of CR-hvKP especially ST11 which need more attention.